Association of prenatal renal ultrasound abnormalities with pathogenic copy number variants in a large Chinese cohort. (1st February 2022) - Su, J.; Qin, Z.; Fu, H.; Luo, J.; Huang, Y.; Huang, P.; Zhang, S.; Liu, T.; Lu, W.; Li, W.; Jiang, T.; Wei, S.; et al.
ABSTRACT: Objectives: To assess the clinical utility of prenatal chromosomal microarray analysis (CMA) in fetuses with abnormal renal sonographic findings, and to evaluate the association of pathogenic or likely pathogenic copy number variants (P/LP CNVs) with different types of renal abnormality. Methods: This was a retrospective study of fetuses at 14–36 weeks screened routinely for renal and other structural abnormalities at the Maternal and Child Health Hospital of Guangxi Zhuang Autonomous Region. We retrieved and analyzed data from fetuses with abnormal renal sonographic findings, examined between January 2013 and November 2019, which underwent CMA analysis using tissue obtained from chorionic villus sampling (CVS), amniocentesis or cordocentesis. We evaluated the CMA findings according to type of renal ultrasound anomaly and according to whether renal anomalies were isolated or non‐isolated. Results: Ten types of renal anomaly were reported on prenatal ultrasound screening, at a mean ± SD gestational age of 24.9 ± 4.8 weeks. The anomalies were diagnosed relatively late in this series, as 64% of cases with an isolated renal anomaly underwent cordocentesis rather than CVS. Fetal pyelectasis was the most common renal ultrasound finding, affecting around one‐third (34.32%, 301/877) of fetuses with a renal anomaly, but only 3.65% ( n  = 11) of these harbored a P/LP CNV (comprising: isolated cases, 2.37% (4/169); non‐isolated cases, 5.30% (7/132)). Hyperechogenic kidney was found in 5.47% ( n  = 48) of fetuses with a renal anomaly, of which 39.58% ( n  = 19) had a P/LP CNV finding (comprising: isolated cases, 44.44% (16/36); non‐isolated cases, 25.00% (3/12)), the highest diagnostic yield among the different types of renal anomaly. Renal agenesis, which accounted for 9.92% ( n  = 87) of all abnormal renal cases, had a CMA diagnostic yield of 12.64% ( n  = 11) (comprising: isolated cases, 11.54% (9/78); non‐isolated cases, 22.22% (2/9); unilateral cases, 11.39% (9/79); bilateral cases, 25.00% (2/8)), while multicystic dysplastic kidney ( n  = 110), renal cyst ( n  = 34), renal dysplasia ( n  = 27), crossed fused renal ectopia ( n  = 31), hydronephrosis ( n  = 98), renal duplication ( n  = 42) and ectopic kidney ( n  = 99) had overall diagnostic rates of 11.82%, 11.76%, 7.41%, 6.45%, 6.12%, 4.76% and 3.03%, respectively. Compared with the combined group of CMA‐negative fetuses with any other type of renal anomaly, the rate of infant being alive and well at birth was significantly higher in CMA‐negative fetuses with isolated fetal pyelectasis or ectopic kidney, whereas the rate was significantly lower in fetuses with isolated renal agenesis, multicystic dysplastic kidney or severe hydronephrosis. The most common pathogenic CNV was 17q12 deletion, which accounted for 30.14% (22/73) of all positive CMA findings, with a rate of 2.51% (22/877) among fetuses with an abnormal renal finding. Fetuses with 17q12 deletion exhibited a wide range of renal phenotypes. Other P/LP CNVs in the recurrent region that were associated with prenatal renal ultrasound abnormalities included 22q11.2, Xp21.1, Xp22.3, 2q13, 16p11.2 and 1q21, which, collectively, accounted for 2.17% (19/877) of the fetuses with prenatal renal anomalies. Conclusions: In this retrospective review of CMA findings in a large cohort of fetuses with different types of renal ultrasound abnormality, the P/LP CNV detection rate varied significantly (3.03–39.58%) among the different types of kidney anomaly. Our data may help in the decision regarding whether to perform prenatal genetic testing in fetuses with renal ultrasound findings. Specifically, prenatal CMA testing should be performed in cases of hyperechogenic kidney, regardless of whether or not the anomaly is isolated, while it should be performed postnatally rather than prenatally in cases of fetal pyelectasis. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.